Comparison of Spin-Echo and Gradient-Echo T1-Weighted and Spin-Echo T2-Weighted Images at 3T in Evaluating Term-Neonatal Myelination - Tyan, A.E. (AJNR Am J Neuroradiol, 2015)
A prior clinical report of 3T MR imaging in subsequently healthy very premature neonates imaged at term-equivalent age found that both gradient recalled-echo–T1WI and spin-echo–T2WI showed higher rates of myelinated structures, compared with spin-echo–T1WI. The current study set out to assess those rates on the same sequences at 3T in term neonates and thus consisted of 16 term neonates with normal-appearing MR imaging findings who subsequently had normal findings at clinical follow-up. Two neuroradiologists independently assessed 19 structures in those infants on all 3 sequences. Gradient recalled-echo–T1WI showed a slightly higher rate of myelination (57.2%–72.4% of all structures) and interobserver agreement (κ = 0.546, P < .0001) than spin-echo–T2WI (58.2%–64.8%; κ = 0.468, P < .0001), while spin-echo–T1WI had the lowest myelination rate and agreement (25.0%–48.4%; κ = 0.384, P < .0001). Both observers noted that the following structures were myelinated in 88%–100% of patients on gradient recalled-echo–T1WI: the brachium of the inferior colliculus, decussation of the superior cerebellar peduncle, habenular commissure, medial lemniscus, pyramidal decussation, posterior limb of the internal capsule, and superior cerebellar peduncle; on spin-echo–T2WI, there was myelination in 88%–100% of the following structures: the brachium of the inferior colliculus, decussation of the superior cerebellar peduncle, inferior cerebellar peduncle, medial lemniscus, and posterior limb of the internal capsule. In conclusion, this study confirmed that similar to the findings in term-equivalent-age premature infants, myelination changes in term neonates may be best assessed on both gradient recalled-echo–T1WI and spin-echo–T2WI at 3T, and not on spin-echo–T1WI.